2014
DOI: 10.1186/s13018-014-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-butyl cyanoacrylate on fracture healing in segmental rat tibia fracture model

Abstract: BackgroundComminuted fractures can occur due to severe traumas. The treatment of these fractures that may cause serious morbidity and sometimes mortality is N-butyl cyanoacrylate. It has been reported that this adhesive provides sufficient rigid fixation for bone healing. This study aims to examine cyanoacrylate radiologically and histologically to determine whether it provides adequate recovery in segmental fractures. The secondary objective is to evaluate N-butyl cyanoacrylate, an adhesive material that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…found that the use of the glue was helpful in treatment of to treat comminuted fractures of the anterior wall of the maxillary sinus which could not easily be treated with internal rigid fixation. Also Akcal et al (1) found that cyanoacrylate was rapidly and easily applied in the segmental fractures and it did not adversely affect fracture healing as seen in biopsies during follow-ups.…”
Section: █ Discussionmentioning
confidence: 98%
“…found that the use of the glue was helpful in treatment of to treat comminuted fractures of the anterior wall of the maxillary sinus which could not easily be treated with internal rigid fixation. Also Akcal et al (1) found that cyanoacrylate was rapidly and easily applied in the segmental fractures and it did not adversely affect fracture healing as seen in biopsies during follow-ups.…”
Section: █ Discussionmentioning
confidence: 98%
“…The studies of Shermak et al [25] and Amarante et al [26] showed that cyanoacrylate created a foreign body reaction in tissues and was resorbed, but had no toxic effect. An experimental study by Akcal et al [27] showed that cyanoacrylate did not adversely affect fracture healing. For the clinical utilization of cyanoacrylate, several studies received favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture model of rats has been used routinely in the laboratory. 25 As reported here, the model served the purpose of showing CLA role in promoting fracture healing. 2.…”
Section: Discussionmentioning
confidence: 99%